1994
DOI: 10.1002/mar.4220110202
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' mood states: The mitigating influence of personal relevance on product evaluations

Abstract: This article reports the results of two studies where subjects' mood states (good, bad) were manipulated. In keeping with previous findings, subjects' evaluations were biased by their mood state. As predicted, however, this bias was only discernible when the product evaluation was perceived to be relatively unimportant. © 1994 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 27 publications
2
41
0
2
Order By: Relevance
“…First, emotions can bias consumers' evaluations of their consumption experiences, as affect has an influence on the coding, storage and retrieval of information linked to these experiences in customers' memory (Bagozzi et al, 1999;Curren and Harich 1994). Such bias was addressed and supported in different studies relating to different service contexts (e.g.…”
Section: Emotions' Role In Customers' Experience Evaluationmentioning
confidence: 99%
“…First, emotions can bias consumers' evaluations of their consumption experiences, as affect has an influence on the coding, storage and retrieval of information linked to these experiences in customers' memory (Bagozzi et al, 1999;Curren and Harich 1994). Such bias was addressed and supported in different studies relating to different service contexts (e.g.…”
Section: Emotions' Role In Customers' Experience Evaluationmentioning
confidence: 99%
“…As a consequence, the recipient processes the message arguments carefully (Pratkanis and Greenwald, 1993) and he uses the result of this processing in his formation of the attitude toward the product (Curren and Harich, 1994;. Thus, under high involvement conditions, the person's evaluation of the strength of the arguments has a direct effect on this person's attitude ) and the person's mood affects the attitude toward the product through the person's processing of the presented arguments (Petty, 1994;Petty et al, 1993;Wegener et al, 1994).…”
Section: The Moderating Effect Of the Customers' Product Involvementmentioning
confidence: 94%
“…The person rather focuses on non-content cues such as the own mood (Petty et al, 1993;Petty and Wegener, 1999;Wegener et al, 1994). Consequently, under low involvement conditions, a person's mood is directly related to this person's attitudes, i.e., people make direct inferences from their mood to the object of interest without thinking about the message arguments (Curren and Harich, 1994;Petty, 1994;Petty et al, 1993). Therefore, transferred to the issue considered here, customers are believed to make direct inferences from their mood to the product recommended by the salesperson in the case of low involvement.…”
Section: The Moderating Effect Of the Customers' Product Involvementmentioning
confidence: 98%
“…Although some studies have shown that mood effects can influence A b for evaluations of low personal relevance (Batra & Stephens, 1994;Curren & Harich, 1994) -presumably owing to an affect-as-information cue bias where mood-state valence is treated as a cue for low-effort judgments (Forgas, 1995) -a stream of empirical research indicates that the effect of feelings is direct upon A ad but indirect upon A b (e.g., Brown et al, 1998;Burke & Edell, 1989). A ad mediates the effect of feelings on A b .…”
Section: H1: (B)mentioning
confidence: 98%
“…This is especially so since research suggests that viewing films and television programs can influence mood states (Curren & Harich, 1994;Gerrards-Hesse, Spies, & Hesse, 1994). Obviously a number of situations exist where consumers may be exposed to advertising when in a happy-mood state, such as watching a favorite television comedy.…”
Section: Mood Definedmentioning
confidence: 98%